Finance PayBuddy: smart payment budgeting application with artificial intelligence (AI) virtual assistant / Amir Sulaiman Sarif ... [et al.] - Sarif, Amir Sulaiman; Roslan, Nurul Shareeza; Zulkarnain, Muhammad; Abdul Rahman, Muhammad Asyraf; Didoh, Teuku Danialdi (Universiti Teknologi MARA, Kedah, 2023)
Recently, it is common of younger generations tend to overspend their budget which leads them to financial loss and debt especially through online payment. Our idea of the innovation is basically to build a smart payment budgeting app with AI virtual assistant that can link with credit or debit cards, and smartwatches via Bluetooth, besides a QR scanner and online transfer to make the app more flexible The main objective is to help younger generations and adults to have a good financial planning and prevent them for overspending. The novelty of our app is users are not only can make a detail monthly budgeting, but they also can automate the payments through AI system by using voice which is less than 30 seconds. If the balance in the budget category is a deficit, the AI will pop up on the phone screen or smartwatch and the alarm will remind the available spending amount. Thus, this app will benefit the society from overspending within their budgets and reduce the probability of financial loss and debt. In the future, the collaboration with the Massachusetts Institute of Technology (MIT) will help to turn our idea into a real new venture.